2021
DOI: 10.1017/s1047951121003668
|View full text |Cite
|
Sign up to set email alerts
|

Prominent prolapsing Chiari network: presentation and prognosis in paediatric patients

Abstract: Chiari network is an infrequently visualized web-like structure in the right atrium that is usually thin and small. Rarely, it can be prominent and elongated with protrusion into the right ventricle during diastole and complications have been reported. Thirty-eight patients (median age 2.5 years) with prolapsing Chiari network were identified and associated cardiac abnormalities documented. Echocardiographic right and left heart parameters were measured and compared to normative data. At presentation, the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…First described by Hans Chiari at the end of the 19th century, it is one of the embryological remnants of the right venous sinus valve ( 9 ). Studies have shown that the Chiari network is related to cardiovascular complications, such as thromboembolism, supraventricular arrhythmia, atrial septal defect, or cyanosis ( 10 , 11 ). The statement that Chiari net causes thromboembolic disease is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…First described by Hans Chiari at the end of the 19th century, it is one of the embryological remnants of the right venous sinus valve ( 9 ). Studies have shown that the Chiari network is related to cardiovascular complications, such as thromboembolism, supraventricular arrhythmia, atrial septal defect, or cyanosis ( 10 , 11 ). The statement that Chiari net causes thromboembolic disease is still controversial.…”
Section: Discussionmentioning
confidence: 99%